Pengenalan Teori-Praktik Komputer Dasar Untuk Anak-Anak Di Desa Tajur Halang Melalui Program KKN - Annisa Putry; Suryana Siregar; Riska Asriwiguna; Siti Khomsatun (Yayasan Pondok Pesantren Sunan Bonang Tuban, 2026)
Computer courses are training programs to help someone learn about computers so that they can understand and operate them properly. Education in Indonesia also requires the use of computers because exams in schools are currently mostly done computer-based, not using paper and pens. However, the understanding and skills of elementary school children in RT 3, RW 07, Dusun Kandang Panjang, Tajur Halang Village, Tajur Halang District, Bogor do not meet the standards. For this reason, the purpose of implementing this program is first to introduce basic computer theory. Second, to teach the practice of using computers from Microsoft Word, Excel and PowerPoint. Activities are carried out once a week with a time span from August 12 to October 10, 2024. The methods used in the implementation are lectures, watching relevant videos, direct practice and interspersed with games and giving incentives and small prizes. After implementing this program, the children in the hamlet can understand the basics of computers well and can operate